The Expert Initiative Right from a Perspective of Legal Hermeneutics - A. A. Boitsov (Теория и практика судебной экспертизы)
The article is devoted to the analysis of one of the rights forming the procedural status of a forensic expert, that is the right of expert initiative. The right is considered not only from a procedural point of view, but also in the context of professional, moral and ethical standards that should guide a forensic expert in his activities. The right of expert initiative is considered as a professional responsibility of an expert. From the perspective of legal hermeneutics an attempt is made to identify its direct recipient and more importantly - the form of realization of this right by the expert. The norm in question is examined within the context of regulatory legal acts and in this connection, we try to understand the content of this norm considering the basic principle of forensic expert activity - the objectivity principle and the complementary principles of comprehensiveness and completeness of a research. The question is raised of the mandatory nature of the norm for the expert regardless of the procedural form of its implementation.